Phenological growth stages of Gaúcho tomato based on the BBCH scale - Fonseca Cardoso, Eliane; Lopes, Allan Remor; Dotto, Marcelo; Pirola, Kelli; Moreno Giarola, Camila (Comunicata Scientiae, 2021)
The phenological growth stages of Gaúcho tomato were firstly described here using the BBCH scale. Based on this general scale, tomato gaúcho phenology showed 8 of 10 principal stages: germination, leaf development, formation of side shoots, inflorescence emergency, flowering, fruit development, maturity of fruit and senescence. A practical use of the scale is proposed, with particular reference to harvest time and management treatments. This scale aims to support farmers and researchers to efficiently plan management practices and experimental treatments.